ANALYSIS OF MACARONI CHIPS SUPPLY CHAIN MANAGEMENT PERFORMANCE IN CV. PUTRA PUTRI JAYA SIDOARJO - Yahya, Azriel; Widayanti, Sri; Wijayati, Prasmita Dian (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2025)
CV. Putra Putri Jaya Sidoarjo is a company that produces macaroni chips. The problem that occurs in the company is the non-achievement of the production plan caused by several factors such as lack of sales, marketing, and the use of poor quality raw materials. The purpose of this study is to map the flow structure of the macaroni chips supply chain in CV. Putra Putri Jaya Sidoarjo. analyze supply chain management performance, and provide improvement recommendations to improve supply chain management performance. The methods used in this study are descriptive analysis, SCOR (Supply Chain Operation Reference) analysis, and AHP (Analytical Hierarchy Process). Descriptive analysis was used to describe the flow structure of the macaroni chips supply chain consisting of the flow of goods, financial flow, and information flow. SCOR and AHP analysis were used to measure and evaluate the performance of macaroni chips supply chain management in CV. Putra Putri Jaya Sidoarjo. The results of this study show that the product flow includes the procurement of raw materials from suppliers, the process of converting raw materials from raw macaroni into macaroni chips, and the process of sending macaroni chips to distributors such as agents, retailers, and wholesalers, to consumers. Financial flows include a variety of financial transactions, such as payments for product purchases, setting credit limits, and scheduling payments. The flow of information includes a variety of information such as raw material inventory, customer preferences, market trends, production and delivery schedules, and product prices. The performance value of supply chain management performance is 90.87 which is included in the excellent category.